Praxis Exiled: Herbert Marcuse and the One Dimensional University. Issue 4 (9th September 2013) - Cunningham, Joseph
<x xml:space="preserve">Abstract</x> Leading Frankfurt School theorist, Herbert Marcuse, possessed an intricate relationship with higher education. As a professor, Marcuse participated in the 1960s student movements, believing that college students had potential as revolutionary subjects. Additionally, Marcuse advocated for a college education empowered by a form of praxis that extended education outside the university into realms of critical thought and action. However, the more pessimistic facet of his theory, best represented in the canonical One Dimensional Man, now seems to be the dominant ideology in the contemporary college experience. With the rise of the corporate university, knowledge is commodified and praxis is supplanted by rampant consumerism. Once a haven for critical theory, the college experience has been overtaken by capitalism, substantially limiting the revolutionary potential for college students in favour of an institutionalised, one dimensional university.